IMPLEMENTATION OF NADIS FOOD AND CATERING WEBSITE USING WATERFALL METHOD - Lodinata, I Wayan Angga Surya; Paramitha, A.A Istri Ita; Putri, I Gst Agung Pramesti Dwi (Jurnal TAM (Technology Acceptance Model), 2024)
Based on research conducted, 86% of people find it difficult to find information about catering, food, suitable prices and so on. So in this case it is necessary to integrate information technology in marketing. In marketing, the use of websites as promotional media is very effective where websites can function as information media. The aim of creating this website is expected to help the owner's performance in the marketing and ordering process. In this research, a system was created using the Waterfall method in building an ordering website for Nadis Food and Catering. The Nadis Food and Catering website functions as a medium for information and catering orders. Where when customers order catering they will be directed to the Nadis Food and Catering admin WhatsApp, this is done in order to establish good communication between customers and Nadis Food and Catering. It is recommended to carry out maintenance in order to increase functional requirements so that the information needed by administrators and users can be met.